Specific Hepatic Sphingolipids Relate to Insulin Resistance, Oxidative Stress, and Inflammation in Nonalcoholic Steatohepatitis - Apostolopoulou, Maria; Gordillo, Ruth; Koliaki, Chrysi; Gancheva, Sofia; Jelenik, Tomas; De Filippo, Elisabetta; Herder, Christian; Markgraf, Daniel; Jankowiak, Frank; Esposito, Irene; Schlensak, Matthias; Scherer, Philipp E; et al. (Diabetes care, 2018)
Insulin resistance and nonalcoholic fatty liver disease have been linked to several lipid metabolites in animals, but their role in humans remains unclear. This study examined the relationship of sphingolipids with hepatic and peripheral metabolism in 21 insulin-resistant obese patients without (NAFL-) or with (NAFL+) nonalcoholic fatty liver and nonalcoholic steatohepatitis (NASH) and 7 healthy lean individuals undergoing tissue biopsies during bariatric or elective abdominal surgery. Hyperinsulinemic-euglycemic clamps with d-[6,6- H ]glucose were performed to quantify tissue-specific insulin sensitivity. Hepatic oxidative capacity, lipid peroxidation, and the phosphorylated-to-total c-Jun N-terminal kinase (pJNK-to-tJNK) ratio were measured to assess mitochondrial function, oxidative stress, and inflammatory activity. Hepatic total ceramides were higher by 50% and 33% in NASH compared with NAFL+ and NAFL-, respectively. Only in NASH were hepatic dihydroceramides (16:0, 22:0, and 24:1) and lactosylceramides increased. Serum total ceramides and dihydroceramides (hepatic dihydroceramides 22:0 and 24:1) correlated negatively with whole-body but not with hepatic insulin sensitivity. Hepatic maximal respiration related positively to serum lactosylceramide subspecies, hepatic sphinganine, and lactosylceramide 14:0. Liver lipid peroxides (total ceramides, sphingomyelin 22:0) and the pJNK-to-tJNK ratio (ceramide 24:0; hexosylceramides 22:0, 24:0, and 24:1) all positively correlated with the respective hepatic sphingolipids. Sphingolipid species are not only increased in insulin-resistant humans with NASH but also correlate with hepatic oxidative stress and inflammation, suggesting that these lipids may play a role during progression of simple steatosis to NASH in humans.